Pengaruh Metode Latihan Small Sided Games terhadap Peningkatan Daya Tahan Aerobik Anak SSB GCR Pati - Muhammad Bagus Misbakhul Muhsinin; Sri Sumartiningsih (MAN Insan Cendekia Jambi, 2026)
This study aimed to analyze the effect of Small-Sided Games (SSG) training on the aerobic endurance of students at the SSB GCR Sukolilo Pati football academy and to determine whether there were differences in aerobic endurance improvement based on gender. An experimental method with a two-group pretest-posttest design was employed. The sample consisted of 30 students aged 13–15 years, selected using purposive sampling. Aerobic endurance was measured using the beep test (20-meter shuttle run). Data were analyzed using descriptive statistics and Repeated Measures ANOVA. The results showed that SSG training had a significant effect on improving aerobic endurance (F(1,28) = 77.778; p < 0.001). Furthermore, while a difference in aerobic endurance existed between male and female participants, there was no difference in the improvement of aerobic endurance following SSG training (F(1,28) = 1.016; p = 0.322). Thus, SSG training is effective for improving the aerobic endurance of adolescent soccer players and yields relatively similar benefits for both males and females.